PREPARING LESSON PLANS BY APPLYING SUSTAINABLE GUIDANCE AT SDN 20 PEKANBARU - Sri Mulyati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the preparation of lesson plans (RPP) by applying sustainable guidance at SDN 20 Pekanbaru. In general, lesson plans (RPP) commonly used by teachers were not following the standard RPP and did not comply with the rules for preparing RPP. This occured due to the lack of the teachers’ ability to prepare the lesson plans. Therefore, it was necessary to carry out continuous guidance by the Principal in preparing RPP and to improve the teachers’ ability. The subjects in this study were 28 teachers at SD 20 Pekanbaru consisting of 22 female teachers and 6 male teachers. The method of this study was School Action Research with 2 (two) cycles. The data were collected through documentation, interviews, observations, and discussions. The results of this study indicated that the score of continuous guidance in cycle I was 1198 with a percentage of 77.8%, while the score in cycle II was 1415 with a percentage of 91.9%. The conclusion was that preparing RPP by implementing continuous guidance improved Teachers’ Competence at SDN 20 Pekanbaru.